2013
DOI: 10.1590/s1677-5538.ibju.2013.05.16
|View full text |Cite
|
Sign up to set email alerts
|

Decline of seminal parameters in middle-aged males is associated with lower urinary tract symptoms, prostate enlargement and bladder outlet obstruction

Abstract: Purpose: We aimed to compare the associations between semen quality, associated reproductive indicators and the main prostate-related parameters in middle-aged men. Materials and Methods: This is a prospective study on 422 middle-aged men who underwent the screening for prostate health. Their reproductive function, semen quality and prostate-related pathologies were investigated. Results: Significant associations between semen quality and prostate-related parameters could be seen. Total sperm count and sperm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
4
0
2
Order By: Relevance
“…At the baseline, age as a risk factor for prostate pathologies showed similar correlation with PSA, TPV and IL-8 in seminal plasma as described recently. [ 12 13 ] Also, associations between seminal inflammatory markers and prostate-related parameters were comparable with findings of recent studies. [ 12 , 14 ]…”
Section: Resultssupporting
confidence: 86%
“…At the baseline, age as a risk factor for prostate pathologies showed similar correlation with PSA, TPV and IL-8 in seminal plasma as described recently. [ 12 13 ] Also, associations between seminal inflammatory markers and prostate-related parameters were comparable with findings of recent studies. [ 12 , 14 ]…”
Section: Resultssupporting
confidence: 86%
“…In such a way it can be assumed the existence of age-induced anomalies in the apoptotic pathway leading to an age-linked increase in sperm cells with higher DNA damage (17). Confirming the contradiction of the literature published results and in spite of what other authors reported (2,3,16,17), we found no decline in sperm concentration levels with advancing age. Sperm DNA damage has been associated to both male aging and infertility and it has been linked to several factors such as oxidative stress, abortive apoptosis and deviations in the process of recombination and protamine replacement during spermatogenesis (8).…”
Section: Discussionsupporting
confidence: 73%
“…Quite a lot of mechanisms have been suggested to explain how advancing age may influence semen quality (3). For instance abnormal semen volume alterations could be caused by seminal vesicle deficiency as vesicle fluid itself largely provides most of the ejaculate volume (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wysoki poziom uszkodzeń DNA może jednak prowadzić do opóźnień cyklu komórkowego i nieprawidłowo naprawionych pęknięć DNA, co ma negatywny wpływ na rozwój ciąży [136]. Zarówno ART, jak i zaawansowany wiek rodzicielski zwiększają szanse na odziedziczenie przez potomstwo uszkodzeń DNA, które prowadzi do negatywnych skutków zdrowotnych [111,119,[137][138][139][140][141][142][143][144][145][146]. W następnych częściach tego rozdziału zostanie wyjaśnione, dlaczego zaawansowany wiek rodziców oraz ART niosą ze sobą wysokie ryzyko uszkodzeń DNA zarodka, w jaki sposób uszkodzenia te negatywnie wpływają na rozwój zarodka i potomstwa oraz jak można ograniczać uszkodzenia DNA.…”
Section: Uszkodzenia Dna W Gametach Zarodkach I U Potomstwa Poczętego...unclassified